Tissue Kidney Injury Molecule-1 Expression in the Prediction of Renal Function for Several Years after Kidney Biopsy - Sanja Simic Ogrizovic (Disease Markers, 2013)
Objectives. Retrospective study was designed to examine the importance of tissue kidney injury molecule-1 (KIM-1) expression in predicting kidney function in sixty patients (27 males) aged 34.15 ± 12.23 years with different kidney diseases over three years after kidney biopsy. Materials and Methods. Tissue KIM-1 expression was determined immunohistochemically and KIM-1 staining was scored semiquantitatively, as well as tubulointerstitialis (TIN), inflammation, atrophy, and fibrosis. Kidney function (MDRD formula) and proteinuria/day were evaluated at the time of biopsy (GFR0) and 6, 12, 24, and 36 months later. Results. Significantly positive correlations between tissue KIM-1 expression and age (r=0.313), TIN inflammation (r=0.456), fibrosis (r=0.317), and proteinuria at 6 months (r=0.394) as well as negative correlations with GFR0 (r=−0.572), GFR6 (r=−0.442), GFR24 (r=−0.398), and GFR36 (r=−0.412) were found. Meanwhile, TIN inflammation was the best predictor of all measured kidney functions during three years, while tissue KIM-1 expression (P=0.016) was a predictor only at 6 months after biopsy. Conclusion. Tissue KIM-1 expression significantly predicts kidney function solely at 6 months after biopsy, when the effects of immune and nonimmune treatments are the strongest.